Single-cell RNA sequencing identifies two fibroblast subtypes and a Trem2+ macrophage subtype as the possible specific cellular targets in abdominal aortic aneurysms - Liu, Zhili; Song, Xiaojun; Wang, Ben; Zeng, Rong; Cui, Liqiang; Zheng, Yuehong; Ye, Wei (Frontiers in Immunology, 2025)
BackgroundAortic aneurysm is a potentially fatal condition. Although contemporary studies have established that this disease triggers an inflammatory response, reduces smooth muscle cells, and induces extracellular matrix remodeling, the involvement of inflammatory cells and associated signaling pathways in the progression and expansion of aneurysms is well-documented. However, clinical treatments utilizing anti-inflammatory therapies have proven ineffective.MethodsIn this study, we employed a classic mouse model of abdominal aortic aneurysm (AAA) to compare the cellular composition and functional phenotypes of normal and AAA cells within a comprehensive single-cell microenvironment.ResultsOur findings revealed distinct evolutionary pathways for both fibroblasts and macrophages, leading to the identification of specific fibroblast subtypes (Fib_Apoc1+/Fabp4+ and inflam-Fib1) and a macrophage subtype (Mac_TREM2). Cellular interactome analysis further reveals that fibroblasts and macrophages may play a certain synergistic role in the development of AAA. This study provides a comprehensive characterization of the transcriptional landscape of AAA and identifies novel therapeutic targets.